Characteristics of treated bamboo/cotton blend yarn produced from ring and rotor spinning techniques - Nor Anuwar, Anis Amirah (2023)
Natural bamboo fibres are coarse and stiff, requiring chemical treatment to reduce their high chemical composition and enhance their textile application, where fine and soft fibres are greatly valued. Cotton fibres are widely used in textile manufacturing due to their comfort and durability. However, the deficiency lies in unsustainable cultivation practices. The blending of bamboo and cotton fibre is beneficial as it combines the desirable qualities of both fibres and producing more environmentally friendly textile products. Three types of treatment were studied to investigate the characteristics of bamboo fibres treated under various chemical treatment conditions. The first type of treatment investigated the effects of varying NaOH concentrations and soaking times. The second type of treatment examined the effects of different NaOH concentrations with constant soaking time and addition of softening treatment. Finally, the third type of treatment studied the effect of constant NaOH concentration with further chemical treatment on bamboo fibre. To examine the morphology of fibre, sliver, and yarn, scanning electron microscope (SEM) was used. The process of making 50:50 treated bamboo/cotton yarn involved several steps, including opening, carding, rotor spinning, and ring spinning. Treatment type 3 produced the most promising fibre for yarn production, with a fineness of 11.2 tex and tenacity of 12.6 cN/tex, resulting in a spinnable 50:50 treated bamboo/cotton yarn. The treated bamboo/cotton ring-spun yarn exhibited the best performance as it promoted higher tensile strength, Young's modulus and tenacity of 58.77 MPa, 8.51 MPa, and 3.66 cN/tex, respectively compared to the rotor-spun yarn